Comparative Hessian Fly Larval Transcriptomics Provides Novel Insight into Host and Nonhost Resistance - Subhashree Subramanyam (MDPI AG, 2021)
The Hessian fly is a destructive pest of wheat. Employing additional molecular strategies can complement wheat’s native insect resistance. However, this requires functional characterization of Hessian-fly-responsive genes, which is challenging because of wheat genome complexity. The diploid Brachypodium distachyon (Bd) exhibits nonhost resistance to Hessian fly and displays phenotypic/molecular responses intermediate between resistant and susceptible host wheat, offering a surrogate genome for gene characterization. Here, we compared the transcriptomes of Biotype L larvae residing on resistant/susceptible wheat, and nonhost Bd plants. Larvae from susceptible wheat and nonhost Bd plants revealed similar molecular responses that were distinct from avirulent larval responses on resistant wheat. Secreted salivary gland proteins were strongly up-regulated in all larvae. Genes from various biological pathways and molecular processes were up-regulated in larvae from both susceptible wheat and nonhost Bd plants. However, Bd larval expression levels were intermediate between larvae from susceptible and resistant wheat. Most genes were down-regulated or unchanged in avirulent larvae, correlating with their inability to establish feeding sites and dying within 4–5 days after egg-hatch. Decreased gene expression in Bd larvae, compared to ones on susceptible wheat, potentially led to developmentally delayed 2nd-instars, followed by eventually succumbing to nonhost resistance defense mechanisms.